Columbia University
IEOR 4404: Simulation
Fall 2009
Solutions to Assignment 5
1. (Exercise 5.14)
(a) Consider
X
with distribution
G
. Since the denominator of the frac
tion is equal to
G
(
b
)

G
(
a
), we can easily guess that the infor
mation we have to use in order to write
F
as a conditional dis
tribution is
a
≤
X
≤
b
.
Let us prove it.
Assume therefore that
F
(
x
) =
P
(
X
≤
x

a
≤
X
≤
b
) and prove that
F
(
x
) =
G
(
x
)
−
G
(
a
)
G
(
b
)
−
G
(
a
)
:
F
(
x
)
=
P
(
X
≤
x

a
≤
X
≤
b
)
=
P
(
X
≤
x

a
≤
X
≤
b
)
P
(
a
≤
X
≤
b
)
P
(
a
≤
X
≤
b
)
=
P
(
X
≤
x, a
≤
X
≤
b
)
P
(
a
≤
X
≤
b
)
using Bayes rule
=
P
(
a
≤
X
≤
x
)
P
(
a
≤
X
≤
b
)
since
x
∈
[
a, b
]
=
G
(
x
)

G
(
a
)
G
(
b
)

G
(
a
)
Therefore, we proved that
F
can be written as
F
(
x
) =
P
(
X
≤
x

a
≤
X
≤
b
).
(b) It is important to notice that the distribution
F
is defined only on the
interval [
a, b
]. Therefore, by differentiating
F
, we obtain the following
density:
f
(
x
) =
F
′
(
x
) =
g
(
x
)
G
(
b
)

G
(
a
)
1
[
a,b
]
(
x
)
.
Now, we have to find an upper bound
c
for the ratio
f
(
y
)
g
(
y
)
for all
y
∈
[
a, b
].
Given the definition of
f
above, it is easy to see that
c
=
1
G
(
b
)
−
G
(
a
)
works. Therefore, we are able to apply the usual ac
ceptance/rejection algorithm to generate
Y
with distribution
F
:
STEP 1. Generate a random variable
X
with distribution
G
.
STEP 2. Generate
U
∼
Uniform[0
,
1]
STEP 3. If
U
≤
f
(
X
)
c g
(
X
)
, then set Y=X. Otherwise, go back to STEP 1.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
This is the end of the preview.
Sign up
to
access the rest of the document.
 Spring '10
 C
 Normal Distribution, Poisson Distribution, Probability theory, Exponential distribution, STEP STEP STEP

Click to edit the document details